The ways of object-oriented program management approach implementation in industrial enterprises activity - Ukrayinets, A. I. (Видавництво Львівської політехніки, 2014)
The article identifies a number of characteristic features notified by domestic and western scientists as inherent for object-oriented program management approach at enterprises. Based on the research of machine building enterprises in Lviv region there are determined the basic tasks for this approach implementation. There has been made an attempt to develop ways of the object-oriented program management approach implementation at industrial enterprises according to their level of competitiveness, strategic priorities, investment options and employees’ professionalism. Виділено ряд характерних ознак, які відзначають вітчизняні та західні науковці, програмно-цільового підходу управління підприємствами. На основі дослідження машино-будівних підприємств Львівщини окреслено основні завдання впровадження цього підходу. Наведено спробу розробити шляхи застосування програмно-цільового підходу управління промисловими підприємствами, відповідно до їх рівня конкурентоспроможності, стратегічних пріоритетів, інвестиційних можливостей та професіоналізму працівників.
Шляхи застосування програмно-цільового підходу управління у діяльності промислових підприємств
Keywords: object-oriented program management approach at enterprise; objectoriented program; program management; industrial enterprises; програмно-цільовий підхід управління підприємством; цільова програма; управління програмами; промислові підприємства